Sarcina ventriculi as the potential cause of abomasal bloat - T.J. Schemm; B.M. DeBey; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1999)
Sarcina-like bacteria, possibly Sarcina ventriculi, have been seen upon histopathologic examination of the abomasums of calves that died of abomasal bloat. The ability of the organism to grow at a low pH and produce large amounts of gas suggests that it may be the cause of abomasal bloat.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Abomasal bloat; Calves; Sarcina ventriculi